Metodologia para valoração tecnológica em universidades - Lorenzoni, Lauren Peres (2019)
Universities are the main responsible for generating knowledge and for scientific and technological progress to occur, it is necessary for them to create and improve the procedures for transferring the knowledge developed to society. Therefore, there is a need to value the technologies developed by means of a specific method that is capable to assisting in the process of technology transfer in universities. Thus, the general objective of the research is to propose a methodology for technological valuation in universities, that it be adaptable to the different areas of knowledge of these institutions. In the methodology, there are two major phases: the first, to measure the qualitative aspects and the second, to measure the quantitative aspects of the technologies developed in universities. In order to measure the qualitative aspects relevant to the technological valuation, which are technological maturity, market potential and institutional approach, a method was developed using Fuzzy logic, because this method allows the use of the knowledge of a Nucleus of Technological Innovation (NTI), with great expertise and later dissemination to other NTIs, with less experience in technological valuation. The result of the qualitative analysis influences the choice of the quantitative valuation method, as well as allows the measurement of non-systematic risk, which is one of the most complex and challenging points in the valuation, which, in addition to the systematic risk, calculated according to Capital Asset Pricing Model (CAPM), results in the rate of return of the technology, directly impacting its valuation. For the quantitative aspects, the usual valuation methods are used and widely discussed in the existing literature, which are costs, market, discounted cash flow and theory of real options. Therefore, the greatest contribution of the research is the methodology developed, which allows to measure the rate of return that the technology has the potential to offer, based on the risks associated with the technology and the market in which it is inserted. It is added the possibility of NIT to carry out a previous analysis of the technology, with subsidies for the elaboration of a proposal with the most convenient commercialization strategy for the technology, as well as the form of more adequate remuneration. Moreover, the qualitative assessment can provide subsidies to NTIs when defining whether a technology should be protected and its protection strategy, it being this phase optimized with the development of a web system.